Sorafenib in patients with refractory or recurrent multiple myeloma - Yordanova, Anna; Hose, Dirk; Neben, Kai; Witzens-Harig, Mathias; Raab, Marc-Steffen; Goldschmidt, Hartmut (Hematological oncology, 2013)
Sorafenib is a small molecular inhibitor of several tyrosine protein kinases, including vascular endothelial growth factor receptor, platelet-derived growth factor receptor and rapidly accelerated fibrosarcoma kinases, targeting signal transduction and angiogenic pathways. It is approved for the treatment of advanced renal cell carcinoma and hepatocellular carcinoma. The objectives of this prospective phase II trial were to assess the activity and tolerability of sorafenib in patients with recurrent or refractory myeloma. In total, 11 patients were enrolled. Patients received 2 × 200 mg of sorafenib orally twice daily until completing 13 full cycles or disease progression. Of the side effects, 8.8% grade 3 and 1.1% grade 4 occurred. Sorafenib treatment was effective in two patients who achieved a partial response and a continuous stable disease with duration of 24.4 months and 6.9 month, respectively. Further clinical investigations are recommended to investigate sorafenib single agent activity in myeloma subgroups with ras-/BRAF-/vascular endothelial growth factor receptor pathway activation and combination therapy approaches.